THE IMPACT OF THE UNIFIED POWER FLOW CONTROLLER ON MAXIMIZATION OF LOADABILITY OF ELECTRIC POWER GRID - SUNDAY ADETONA; RAIFU SALAWU; FRANK OKAFOR; JOSEPH ADEYEMI (Journal of Engineering Studies and Research)
The building of additional transmission network to meet the demand of the ever-increasing load is expensive, and time consuming. An alternative to constructing new lines is the incorporation of the Flexible Alternating Current Transmission System (FACTS); in which a Unified Power Flow Controller (UPFC) is a member of the ménage, which can be modelled as a combination of Static Var Compensator and Thyristor Control Series Compensator. This study determines the optimal location of the UPFC by randomly adding loads to the existing transmission network until the Fast Voltage Stability Index of one of the lines is at a critical point. This is the vital line in which UPFC components are added. The sizing of the components of the UPFC is determined using Artificial Bee Colony algorithm. The IEEE 30-bus network is exploited as the test bed. The results obtained reveal that the optimal positioning and sizing of the UPFC for the purpose of maximizing loadability of the grid when load angles are assumed to be negligible are the same as when the load angles are considered. The loadability of the test bed when UPFC is not injected in the grid is 440.376 MW, whereas, it is 837.915 MW when the UPFC is optimally located and sized; and this represents 90.27 %. The sizes of the shunt and series components of the UPFC that assist in realizing this maximization are -0.2780 pu and 0.1000 pu respectively.